2005
DOI: 10.1177/000313480507100709
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Bypass via Resternotomy after Pectus Excavatum Repair

Abstract: Pectus excavatum is a chest wall deformity that commonly warrants pediatric surgical correction for cosmesis or respiratory impairment via sternotomy. The repair typically consists of sternal wedge osteotomy and subsequent placement of a Steinman pin across the sternum with fixation to the ribs bilaterally. Coronary artery bypass grafting (CABG) after surgical repair of the sternum with a metal implant poses an intriguing surgical challenge. Literature review reveals only one such previously described case. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In our literature review, we only found a few reports of patients with a history of pectus excavatum repair who underwent cardiac surgery, as well as cases of patients with a history of cardiac surgery who underwent recardiac surgery and pectus excavatum repair in parallel (Table 1). [2][3][4][10][11][12][13][14] In the past decades, numerous surgical techniques have been developed for the correction of the pectus excavatum. Although the most well-known is the Ravitch procedure, studies on performing cardiac surgery after the Ravitch procedure are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In our literature review, we only found a few reports of patients with a history of pectus excavatum repair who underwent cardiac surgery, as well as cases of patients with a history of cardiac surgery who underwent recardiac surgery and pectus excavatum repair in parallel (Table 1). [2][3][4][10][11][12][13][14] In the past decades, numerous surgical techniques have been developed for the correction of the pectus excavatum. Although the most well-known is the Ravitch procedure, studies on performing cardiac surgery after the Ravitch procedure are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are some reports of the first sternotomy for cardiac surgery in a patient with pectus excavatum [1] and simultaneous cardiac surgery and repair of pectus excavatum [2], median sternotomy after sternoturnover has been rarely reported. Mohan et al [3] performed CABG through sternotomy after sternal elevation with metal implant and noted that some surgeons recommend avoiding sternotomy as a repeat approach to the mediastinum. Kanaoka et al [4] reported a case of median sternotomy for aortic surgery 13 years after sternoturnover, followed by flail chest and 15-day mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%